A Robust Auto-Tuning PID Controller Design based on S-Shaped Time Domain Response - Yumuk, Erhan; Copot, Cosmin; Ionescu, Clara M. (IEEE, 2022)
Abstract: In this study, a revisited improved approach of an initial frequency response based autotuner is proposed to enable PID controller design based on S-shaped step response data. In prior autotuner, the critical frequency value is found using relay test whereas process frequency response and its derivative at this frequency are calculated via the sine test. With the proposed approach, these values are estimated using the first order plus time delay models, which are employed to characterize S-shaped step response. Firstly, an identification method is used to find the model parameters, i.e. time constant T and delay time L. Secondly, the required values are estimated using the first order plus time delay model. The remaining tuner design steps are the same as in the prior autotuner. The simulations are performed on four different types of dynamical systems to show effectiveness of the proposed approach. The simulation results suggest that the performance of the control system using the proposed approach improves in terms of achievable performance indicators such as overshoot and settling time.
Keywords: Computer. Automation; Economics; Mathematics